(untitled) (Świat Idei i Polityki, 2005)
Unlike in the past, the local development, including the direction, pace and quality aspects, may depend not only on external conditions and global processes but also on the scale and way the inhabitants of a given area participate in its creation and maintaining. However, the participation and the activity should not be formal but real. Then we can define the system as democratic, particularly as far as the territorial self-government is concerned, which, in the author's opinion, appears to be the most common and the most important for the sphere of social practice and experiment in Poland. The self-government with its immanent characteristic may become either a main accelerator or a very effective inhibitor, may strengthen or waste the potentials of the community and citizens. Today this truth is commonly realized and occurs in the theory of planning and managing the local development. Controversy appears in practical approach which is not only far from democratic assumptions but also from the pragmatics and praxeology of the effective social activity in general. In its rational collective activity directed to an aim (at least it should be like this), social participation fulfils a series of constitutive and constructive functions.